The Relationship of Environmental Management Accounting, Environmental Strategy and Managerial Commitment with Environmental Performance and Economic Performance - Christine, Debbie; Yadiati, Winwin; Afiah, Nunuy Nur; Fitrijanti, Tettet (International Journal of Energy Economics and Policy, 2019)
Nowadays, carbon and other ozone harming emanations are one of the fundamental drivers of this overshoot. In the light of this discussion, the current examination aims to investigate the relationship between accounting, management and environment in realizing firm performance. In doing so, the current examination opted to inspect the critical relationship of environmental management accounting (EMA), environmental strategies (ENS) and managerial commitment (MAC) in driving firm performance. Given the concerns within the literature that environmental processing within organization enhance financial costs, the authors of the study are motivated to analyze the impact of the variables on both environmental and economic performance of SMEs in Indonesia. We apply novel partial least square structural equation modelling by collected the data from 317 respondents of different small and medium size enterprises of Indonesia. The results of SEM confirm that economic performance and environmental performance have significantly and positively impacted by environmental strategy. The outcomes of partial least square structural equation modelling also indicate that economic and environmental performance have also positively and significantly impacted by the environmental management accounting. Finally, the results of PLS-SEM also specified that economic performance and environmental performance have significantly and positively affected by managerial commitment. Keywords: Environmental Strategy, Managerial Commitment, Environmental Management Accounting. JEL Classifications: Q55, Q50 DOI: https://doi.org/10.32479/ijeep.8284